Novel variant in the KCNK9 gene in a girl with Birk Barel syndrome - Šedivá, Marie; Laššuthová, Petra; Zámečník, Josef; Sedláčková, Lucie; Seeman, Pavel; Haberlová, Jana (European journal of medical genetics, 2020)
Birk Barel syndrome also known as KCNK9 imprinting syndrome is a rare developmental disorder associated with a loss-of-function variant in KCNK9, an imprinted gene with maternal expression on the 8th chromosome encoding the TASK3 (TWIK-related acidity inhibited K + -channel 3). Only two variants of KCNK9 have been associated with this condition before, both of them leading to the same amino-acid exchange p.Gly236Arg (Barel, 2008, Graham, 2016). We describe a case of a 17-year-old girl presenting with very similar phenotype and pure motor neuropathy with a novel variant c.710C > A: p.Ala237Asp (NM_001282534.1) in KCNK9 found by whole exome sequencing. Our case suggests that Birk Barel syndrome may not be caused only by variants leading to amino-acid exchange p.Gly236Arg but also by other missense variant in this gene and that peripheral motor neuropathy might be a feature of this syndrome.
Keywords: Mutation, Missense; genomový imprinting; Male; Intellectual Disability; Genetic Predisposition to Disease; missense mutace; Adolescent; sekvenování exomu; Amino Acid Sequence; mužské pohlaví; svalová hypotonie; mentální retardace; mladiství; lidé; ženské pohlaví; Humans; Potassium Channels, Tandem Pore Domain; Genomic Imprinting; sekvence aminokyselin; Female; Exome Sequencing; kraniofaciální abnormality; genetická predispozice k nemoci; Muscle Hypotonia; Craniofacial Abnormalities; draslíkové kanály s dvoupórovou doménou